Exploration technology of archaeological objects by the method of drilling - Vietrov, Victor (Archaeologia Lituana, 2025)
We represent the results of archaeological works by using the drilling method. Such works were carried out in the Medzhybizh and Bar castles, as well as in Palaeolithic field explorations. Our drilling research in castles focused on the inspection of courtyards and fortification of castles. Drilling made it possible to see the thickness of cultural layers up to 8 meters of thick. Based on the obtained data, reconstructions of the daytime surface of castle courtyards and the sequence of changes in their relief were carried out. Drilling during the search for Palaeolithic sites was carried out on turfed areas and different soil types. The high efficiency of exploratory drilling operations has been determined. The equipment was adapted, and the optimal drilling technique worked out during archaeological explorations.
Keywords: drilling methods; Medzhybizh; Bar; castles; Palaeolithic